Effectiveness of short sprint interval training in women with major depressive disorder: a proof-of-concept study - Ribeiro, Jéssica Alves; Schuch, Felipe Barreto; Tonello, Laís; Meneghel Vargas, Kleber F.; Oliveira-Junior, Silvio A.; Müller, Paulo T.; Boullosa, Daniel (Frontiers in Psychiatry, 2024)
Background High-intensity intermittent training has emerged as an option for treating major depressive disorder (MDD). However, short sprint training (sSIT), an efficient HIIT modality, has not been tested yet for this purpose. The sSIT has been proven to induce the same metabolic adaptations, with the advantage of promoting lower muscle fatigue than other HIIT protocols. Methods Seventeen adult women diagnosed with moderate/severe MDD were randomly allocated into a sSIT group (n=9) or a control condition (n=8). The sSIT group completed, over two weeks, six 6-10-min sessions which consisted of 3-12 “all out” sprints of 5 s interspersed with low-intensity recovery of 30-45 s. The week before and after the intervention, both groups were evaluated with the Hamilton Depression Rating Scale of 21-itens (HAM-D21), and for physical fitness and incidental physical activity. Results The sSIT group exhibited significant improvements for HAM-D21 scores (24.6±8.2 vs. 16.8±10.1), maximum aerobic power (140±15 vs. 155±15 W), countermovement jump (13.0±3.4 vs. 14.9±3.1 cm), % of body fatness (32.4±4.4 vs. 29.3±3.8%), and 4-days number of steps (13,626±11,309 vs. 16,643±15,371) after the training period when compared to the control group. Conclusion Less than 1 hour of a sSIT protocol over two weeks have demonstrated to reduce depressive symptoms, while improving aerobic fitness and body composition, and increasing incidental physical activity in a sample of women diagnosed with MDD.